World record: Single AMS 800 artificial urinary sphincter functioning uninterrupted for 29 years in male paraplegic patient - Rehder, Peter (Urol Case Rep, 2020)
Lapides has revolutionized the treatment of neurogenic patients by introducing routine intermittent catheterization in 1971. This drastically lowered mortality from urosepsis. Scott introduced the artificial urinary sphincter (AUS) in 1972. This gave a completely new perspective for incontinent patients by dramatically increasing the quality of life. In patients with neurogenic urinary incontinence, the principles of care are preserving renal function, maintaining a low-pressure reservoir, allowing unobstructed urine flow and providing continence. We describe a male patient that received an AUS with a bladder neck cuff that functioned without revision for 29 years. After 30 years, AUS exchange proved successful.